Evaluation of the Antimicrobial Efficacy of Triphala, Aloe Vera, and Morinda Citrifolia (M. Citrifolia) as Potential Root Canal Irrigants and their Effectiveness in Decontaminating Gutta-Percha Cones: AnIn vitroDisk Diffusion and Digital Photo-Colorimeter-Based Study - Satyarth, Saurabh; Subramani, Savadamoorthi; Ganesan, S.; Swathika, B.; Sadananda, Vandana; Chikkanna, Meenakumari; Suresh, Babu; Swarnalatha, C; Nayyar, Abhishek (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context and Aim: A plethora of chemicals have been used for gutta-percha decontamination, though none of these methods have proven to be fully effective. The aim of this study was to evaluate the antimicrobial efficacy of triphala, aloe vera, and Morinda citrifolia (M. citrifolia) as potential root canal irrigants and their effectiveness in decontaminating gutta-percha cones against Escherichia coli (E. coli), Escherichia faecalis (E. faecalis), and Staphylococcus aureus (S. aureus). Materials and Methods: The antimicrobial efficacy of different herbal extracts against the reference strains of the test pathogens was assessed based on the zones of inhibition created, while for testing decontamination of gutta-percha cones, sterile gutta-percha cones were incubated in thioglycollate broth (THIO) followed by the evaluation of the turbidity values of the broth (in formazin turbidity units (FTU)) through digital photo-colorimeter. Statistical Analysis Used: One-way analysis of variance (ANOVA) and Fisher’s least significant difference (LSD) post hoc analysis were used for comparison between different groups.P<0.05 was considered statistically significant. Results: The results of this study revealed that for E. faecalis andE.coli, 90% ethanolic extracts of aloe vera had maximum efficacy with the diameter of the zone of inhibition achieved being 23.0 mm and 17.0 mm, respectively, while forS.aureus, both aloe vera and M. citrifolia showed equal zones of inhibition of diameter of 22.0 mm at 10-1concentration. Conclusions: The results obtained in this study suggested that all three tested herbal extracts were found to have optimal antimicrobial activity against the test pathogens.